Takayasu arteritis with middle aortic syndrome and mesenteric ischemia treated by aortic stenting - Sarah Morrissey, MD, MA, FRCSC; Kong Teng Tan, MD, FRCS, FRCR, FRCPC; John Stephen Byrne, MB BCh BAO, FACSI (Journal of Vascular Surgery Cases and Innovative Techniques, 2017)
A 48-year-old woman suffering from Takayasu arteritis presented with middle aortic syndrome consisting of abdominal pain, refractory hypertension with pulmonary edema and pleural effusions, and lower limb ischemia. She failed to improve with high-dose steroid therapy and underwent endovascular stenting of two severe stenoses in the supraceliac and infrarenal aorta. Her symptoms resolved and hypertension improved after the procedure.